Basic psychological needs theory as a framework for effective mental health referrals in collegiate sport: A grounded theory investigation - Ugrenovi, L.; Voelker, D. K.; Coker-Cranney, A. M.; Raabe, J.; Zaisberger, V. (Journal of Clinical Sport Psychology, 2026)
Although the mental health referral aims to connect athletes to appropriate resources, referral guidelines are often focused on procedure without strategies for facilitating desirable outcomes. Using grounded theory, 14 collegiate athletes were interviewed to explore their referral experiences and explain those experiences using basic psychological needs theory. The grounded theory showed that proactive referrals and attending to athletes` prereferral experiences were central to supporting participants` relationship with mental health. Referrals characterized by need satisfaction helped participants disconnect their mental health concerns from self-perception and pursue services. Some participants reinternalized mental health stigma upon reengagement with unsupportive environments, even following positive referral experiences. Need thwarting was associated with poorer outcomes. The grounded theory suggests basic psychological needs theory is a promising framework for referral guidance that should be tailored to athletes` unique contexts. Study insights support mental health providers in educating others on referral processes that contribute to positive mental health culture in sport.